Digital Ensemble: The EN. (1st March 2017) - Flanagan, Eilis; Hall, Tony
Abstract: This article outlines the ENaCT educational design for Digital Ensemble, an innovative approach to English assessment integrating drama pedagogy with mobile computing (e.g. iPad). ENaCT represents the key themes that framed and informed the research: ensemble, narrative, collaboration and technology. Starting with ENaCT as a prototype concept design for the development and evaluation of technology-enhanced embodied assessment in English, the research developed and refined the model through collaborative cycles of design with post-primary schools. The design-based research study reported here was undertaken in three significant design iterations, totalling 15 weeks and 85 teaching hours. 131 Irish Senior Cycle students, aged 15 to 17 participated: 45, 46 and 45 pupils respectively in iterations one, two and three. Two teachers participated throughout. The article outlines for English teachers and educational designers the adaptable ENaCT framework for Digital Ensemble, including design and assessment criteria and evaluation rubrics, illustrated by exemplars of pupils' work.